2017
DOI: 10.1128/mbio.01931-17
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Activity of the Salmonella Invasion-Associated Injectisome Reveals Its Intracellular Role in the Cytosolic Population

Abstract: The Salmonella invasion-associated type III secretion system (T3SS1) is an essential virulence factor required for entry into nonphagocytic cells and consequent uptake into a Salmonella-containing vacuole (SCV). While Salmonella is typically regarded as a vacuolar pathogen, a subset of bacteria escape from the SCV in epithelial cells and eventually hyperreplicate in the cytosol. T3SS1 is downregulated following bacterial entry into mammalian cells, but cytosolic Salmonella cells are T3SS1 induced, suggesting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 71 publications
(146 reference statements)
1
26
1
Order By: Relevance
“…To better understand this post-entry role of SipA in epithelial cells, we first compared proliferation of WT Salmonella and an isogenic ΔsipA mutant in HeLa cells using two complimentary approaches (gentamicin protection assays vs real time imaging). In agreement with previous studies (Brawn et al, 2007;Klein et al, 2017), the gentamicin protection assay showed that, at 6-8 h pi, the ΔsipA mutant has a proliferation defect (Fig. 1A).…”
Section: Sipa Promotes Proliferation Of Cytosolic Salmonellasupporting
confidence: 93%
See 3 more Smart Citations
“…To better understand this post-entry role of SipA in epithelial cells, we first compared proliferation of WT Salmonella and an isogenic ΔsipA mutant in HeLa cells using two complimentary approaches (gentamicin protection assays vs real time imaging). In agreement with previous studies (Brawn et al, 2007;Klein et al, 2017), the gentamicin protection assay showed that, at 6-8 h pi, the ΔsipA mutant has a proliferation defect (Fig. 1A).…”
Section: Sipa Promotes Proliferation Of Cytosolic Salmonellasupporting
confidence: 93%
“…Other activities that have been attributed to SipA include Caspase‐3 cleavage and activation (Cain et al , ; McIntosh et al , ), induction of CXC chemokine expression through phosphorylation of IL‐8‐transcription regulatory proteins, JUN and p38MAK (Figueiredo et al , ) and promoting fusion with early endosomes (Singh et al , ). Of relevance to this study, several groups have shown that SipA is also involved in intracellular replication, with the consensus being that it promotes vacuolar replication (Brawn et al , ; Klein et al , ; Singh et al , ; Zhang et al , ). Here, we found that SipA has no effect on replication per se .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…time points if the SPI1‐T3SS was functional. A later study used a system for controlled SPI1‐T3SS activity in intracellular Salmonella and observed a role of effector proteins SopB and SipA in cytosolic proliferation (Klein et al, ). Our data show that the SPI1‐T3SS is involved in damage of the early SCV, and we propose a key role of SopE in the early phase of internalisation and intracellular presence.…”
Section: Discussionmentioning
confidence: 99%